Statistical assessment of in vitro drug release kinetics and quality evaluation of desloratadine orally disintegrating generic tablets available in Bangladesh. (March 2021) - Shuma, Madhabi Lata; Halder, Shimul
The objective of the present study was to compare the in vitro equivalence of different orally disintegrating tablets (ODT) of Desloratadine (DES) available in Bangladesh pharmaceutical market with the reference brand. The in vitro dissolution study was carried out using the United States Pharmacopoeia (USP) paddle method and a comparative study were also carried out with the reference brand. Other pharmacopoeial and non-pharmacopoeial quality assessment parameters including hardness, friability, water absorption ratio, and disintegration time etc. were also evaluated. From the results of the dissolution profile of the commercially available products, it found majority of the products didn't exhibited compendial requirements in dissolution behavior to the reference brand with model-independent approach ( f 2 > 50, f 1 < 15) and showed statistically significant differences. Additionally, the data of different physical quality parameters revealed that all commercial products complied with the official specifications. From these findings, it could be suggested that the DES-ODT formulations' available in the Bangladesh market could be prescribed; however additional experiments might require to clarify the interchangeability among the products.